Quality system study on Moldex Philippines - Dela Cruz, Ma. Alesandra K.; Gangoso, Cesar K. III; Villarin, Andrea F.; Villegas Camilla B. (College of Engineering, 1999)
The principal objective of this study is to evaluate and improve the existing quality system of Moldex Products Philippines, Inc. Basically, the study is divided into two major phases. Phase I is an extensive documentation of the company's existing quality system, while Phase II is an evaluation of the quality control process. In Phase I, a key product was selected and the Failure Mode and Effects Analysis (FMEA) method was used for preliminary evaluation. In phase II, a pareto analysis was performed on the quality system. The analysis substantiated the need to focus the study on the extrusion process. A stability and capability study was performed by the researchers to give an in-depth and quantitative assessment of the extrusion process. The stability study revealed that the process is in a state of statistical control. On the other hand, the capability study revealed that the process failed to meet its potential capability. Utilizing the fishbone and streamline analysis, areas for improvement were determined. A quality cost analysis was also done to evaluate existing quality cost. Finally, recommendations were summarized and a short-term and long-term implementation program is presented.